Odontogenic Myxoma of the Mandible - Manne, Rakesh Kumar (Hindawi Publishing Corporation, 2012)
Odontogenic myxomas are benign but locally aggressive neoplasms found almost exclusively in the jaws and arise only occasionally in other bones. We present a rare case of odontogenic myxoma occurring in the mandible of a 19-year-old male patient with a brief review of clinical and radiological features, and diagnostic and operative dilemmas in managing the same.